A longitudinal blended learning curriculum for bedside ultrasound education in pulmonary and critical care fellowship - Harry Kuperstein; Kunal Gada; Werda Alam; Sahar Ahmad (BMC Medical Education)
Abstract Background There exists no standardized longitudinal curriculum for teaching bedside ultrasonography (US) in Pulmonary and Critical Care Medicine (PCCM) fellowship programs. Given the importance of mastering bedside US in clinical practice, we developed an integrated year-long US curriculum for first-year PCCM fellows. Methods 11 first-year PCCM fellows completed the entire seven-step Blended Learning Curriculum. We provide results from an evaluation of Step I, the initial training course. Evaluation included a 17-question multiple-choice knowledge test and a hands-on skill exam delivered pre-, immediately post-, and 6 months post-course. Performance on these same evaluation measures was compared between learners who completed a traditionally designed curriculum, which contained a formal in-person didactic course, and learners who completed a blended learning curriculum covering the same learning objectives. Results All learners showed a significant improvement immediately after the course in both knowledge (p = 0.007) and skills (p = 0.004) with adequate retention of both knowledge and skills after 6 months. Scores on a multiple-choice knowledge test increased from a median (interquartile range [IQR]) of 24% (15–41%) pre-course to a median of 71% (59–82%) post-course, while scores on a hands-on skill exam increased from a median of 16% (7–45%) pre-course to a median of 87% (74–94%) post-course. There was no difference in learning or retention between those who learned via the blended learning model as compared with a more traditional model. Learners agreed the course was well-designed, with relevant learning topics, sufficient time to learn, and fair evaluation modalities. The blended learning model required 15 fewer faculty-hours than the traditional learning model. Discussion A blended learning model for bedside US education implemented at a single PCCM fellowship performs comparably to a traditional model for both acquisition and retention of knowledge and skills. The incorporation of asynchronous learning mitigates the barrier of insufficient time and quantity of US skilled teaching faculty that many PCCM fellowships face and provides flexibility to both instructors and learners.